Measuring the Joint Distribution of Household's Income, Consumption and Wealth Using Nested Atkinson Measures - Ruiz, Nicolas (OECD Publishing, 2011)
Following recommendations from the Stiglitz-Sen-Fitoussi Commission (2009), this paper proposes the use of a new methodology to measure the joint distribution of households. income, consumption and wealth. Based on a multidimensional extension of the Atkinson generalized mean framework, the paper justifies the application of this methodology based on a set of standard and acknowledged properties, proving that this is the sole methodology satisfying them all simultaneously. The derived multidimensional index has an intuitive structure, which allows evaluating the overall material conditions of households under different perspectives and with varying sensitivity to distributionnal issues. Under its general form, the index encompasses a class of sub-indices that impose various restrictions on its parameters; the paper discusses the extent to which different restrictions on parameters affect the multidimensional assessments of various population groups, and provides some empirical illustrations using those different specifications. The question addressed by the multidimensional measure presented here is whether the joint consideration of household income, consumption and wealth modifies substantially the picture of material living standards of different individuals and groups relative to the one provided by income alone. Based on the dataset used here, the paper provides strong evidence on the importance of such a multidimensional assessment
Keywords: Economics